1993
DOI: 10.1111/j.1476-5381.1993.tb13800.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the novel nonpeptide angiotensin II receptor antagonist, BIBR 277

Abstract: The pharmacological profile of BIBR 277, 4′‐[(1,4′‐dimethyl‐2′‐propyl[2,6′‐bi‐1H‐benzimidazol]‐1′‐yl)methyl]‐[1,1′‐biphenyl]‐2‐carboxylic acid, a novel, nonpeptide angiotensin II receptor antagonist has been investigated by use of receptor binding studies, enzymatic assays, functional in vitro assays in rabbit aorta as well as in vivo experiments in pithed, anaesthetized and conscious rats. BIBR 277 potently interacted with rat AT1 receptors (Ki 3.7 nm). Competitive receptor interaction was shown by radioligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
114
2
7

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 31 publications
4
114
2
7
Order By: Relevance
“…[10][11][12][13][14][15] These studies have found that while candesartan (0.01-1 nM) produces a clear dose-dependent reduction in the maximal contractile response to angiotensin II (characteristic of insurmountable or non-competitive antagonism), 15 losartan and eprosartan are displaced from the AT 1 receptor with increasing doses of angiotensin II and cause parallel shifts of the dose response without affecting the maximal effect of angiotensin II (competitive or surmountable antagonism). 10,11,14 Valsartan, irbesartan and EXP-3174 (the active metabolite of losartan) exhibit mixed-type competitive (or surmountable) and non-competitive (insurmountable) antagonism at the AT 1 receptor; 11,12 telmisartan exhibits insurmountable (non-competitive) but reversible inhibition to angiotensin II-induced contractions in isolated rabbit aortic tissue.…”
Section: Antagonistic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] These studies have found that while candesartan (0.01-1 nM) produces a clear dose-dependent reduction in the maximal contractile response to angiotensin II (characteristic of insurmountable or non-competitive antagonism), 15 losartan and eprosartan are displaced from the AT 1 receptor with increasing doses of angiotensin II and cause parallel shifts of the dose response without affecting the maximal effect of angiotensin II (competitive or surmountable antagonism). 10,11,14 Valsartan, irbesartan and EXP-3174 (the active metabolite of losartan) exhibit mixed-type competitive (or surmountable) and non-competitive (insurmountable) antagonism at the AT 1 receptor; 11,12 telmisartan exhibits insurmountable (non-competitive) but reversible inhibition to angiotensin II-induced contractions in isolated rabbit aortic tissue.…”
Section: Antagonistic Propertiesmentioning
confidence: 99%
“…10,11,14 Valsartan, irbesartan and EXP-3174 (the active metabolite of losartan) exhibit mixed-type competitive (or surmountable) and non-competitive (insurmountable) antagonism at the AT 1 receptor; 11,12 telmisartan exhibits insurmountable (non-competitive) but reversible inhibition to angiotensin II-induced contractions in isolated rabbit aortic tissue. 13 The antagonistic properties of candesartan, irbesartan, losartan and its active metabolite EXP-3174 were compared by Morsing and colleagues ( Figure 2). 16 The investigations were conducted in isolated preparations of rat portal vein and rabbit thoracic aortic strips using concentrations of antagonists equivalent to the (non-protein-bound) plasma concentrations achieved with oral dosing.…”
Section: Antagonistic Propertiesmentioning
confidence: 99%
“…The compound is not metabolized by cytochrome P450 isoenzymes and has a low risk for P450-based drug interactions. 37,38 A relevant fact to be noted is that unlike other ARBs, where up to 50% of the dose is excreted by the kidney, only 1% of a telmisartan dose in excreted by the kidney. Therefore renal impairment is unlikely to affect the pharmacokinetics of telmisartan.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Sprawia to, że redukcja zarówno wartości skurczowego (SBP), jak i rozkurczowego (DBP) ciśnienia tętniczego powodowana podaniem telmisartanu nie koreluje ze spadkiem częstotliwości rytmu serca. Obserwuje się natomiast wywołany zastosowaniem leku rozkurcz mięśniówki gładkiej naczyń krwionośnych (w tym także aorty), wzrost przepływu krwi przez nerki i zwiększenie natriurezy [12,13]. U pacjentów z uprzednio nieleczonym nadciśnieniem tętniczym, którzy stosowali ściśle monitorowaną dietę, obejmującą spożycie sodu w ilości 100 mmol/d., wydalanie sodu z moczem dzięki podawaniu telmisartanu było znacznie zwiększone.…”
unclassified